Stepwise pH control to promote synergy of chemical and biological processes for augmenting short-chain fatty acid production from anaerobic sludge fermentation. (15th May 2019) - Wang, Xu; Li, Yanbo; Zhang, Ya; Pan, Yi-Rong; Li, Lin; Liu, Junxin; Butler, David
Abstract: Although sludge-converted short-chain fatty acids (SCFAs) are promising feedstocks for biorefineries, it remains challenging to maximise SCFA production by enhancing synergies between chemical/biological hydrolysis and acidogenesis processes while employing a balanced composition of microbial communities to counteract methanogenesis. Herein, stepwise control of fermentation pH and chemical/microbiological composition analysis of fermented sludge were used to probe the underlying mechanisms of SCFA production. Fermentation at pH 11 during the first three days promoted both chemical and microbial hydrolysis of sludge proteins and provided a niche for Anaerobrancaceae sp. to transform soluble protein into SCFAs. When pH was decreased from 11 to 9, Acinetobacter, Proteiniborus, Proteiniclasticum, and other acetogens became predominant and stayed significantly more active than during first-stage fermentation at pH 11, which benefited the acidification of hydrolysed substrates. Further assays indicated that early-stage sludge fermentation at pH 11 decreased the total amount of methanogenic archaea and hence reduced the amount of SCFAs consumed for methane production. Thus, the use of stepwise pH control for sludge fermentation allowed one to establish process synergies, facilitate chemical and biological hydrolysis, inhibit methanogens, and promote the growth of acidifying bacterial communities, which resulted in efficient SCFA production from sludge. Graphical abstract: Image 1 Highlights: Augmentation of SCFA yield from anaerobic sludge fermentation was investigated. The SCFA yield increased with the studied fermentation pH stepwise strategy. The studied strategy greatly promoted synergy of chemical and biological processes. A conceptual model was proposed to better understand the underlying mechanism.